Anti-sulfatide antibody-related Guillain–Barré syndrome presenting with overlapping syndromes or severe pyramidal tract damage: a case report and literature review - Ji, Xiaotian; Zhu, Jiaqian; Li, Lujiang; Yang, Xiaodan; Zhou, Shaolong; Cao, Liming (Frontiers in Neurology, 2024)
Introduction Anti-sulfatide antibodies are key biomarkers for the diagnosis of Guillain–Barré syndrome (GBS). However, case reports on anti-sulfatide antibody-related GBS are rare, particularly for atypical cases. Case description, case 1 A 63 years-old man presented with limb numbness and diplopia persisting for 2 weeks, with marked deterioration over the previous 4 days. His medical history included cerebral infarction, diabetes, and coronary atherosclerotic cardiomyopathy. Physical examination revealed limited movement in his left eye and diminished sensation in his extremities. Initial treatments included antiplatelet agents, cholesterol-lowering drugs, hypoglycemic agents, and medications to improve cerebral circulation. Despite this, his condition worsened, resulting in bilateral facial paralysis, delirium, ataxia, and decreased lower limb muscle strength. Treatment with intravenous high-dose immunoglobulin and dexamethasone resulted in gradual improvement. A 1 month follow-up revealed significant neurological sequelae. Case description, case 2 A 53 years-old woman was admitted for adenomyosis and subsequently experienced sudden limb weakness, numbness, and pain that progressively worsened, presenting with diminished sensation and muscle strength in all limbs. High-dose intravenous immunoglobulin, vitamin B1, and mecobalamin were administered. At the 1 month follow-up, the patient still experienced limb numbness and difficulty walking. In both patients, albuminocytologic dissociation was found on cerebrospinal fluid (CSF) analysis, positive anti-sulfatide antibodies were detected in the CSF, and electromyography indicated peripheral nerve damage. Conclusion Anti-sulfatide antibody-related GBS can present with Miller–Fisher syndrome, brainstem encephalitis, or a combination of the two, along with severe pyramidal tract damage and residual neurological sequelae, thereby expanding the clinical profile of this GBS subtype. Anti-sulfatide antibodies are a crucial diagnostic biomarker. Further exploration of the pathophysiological mechanisms is necessary for precise treatment and improved prognosis.